2018
DOI: 10.1159/000493387
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island Methylator Phenotype May Predict Poor Overall Survival of Patients with Stage IV Colorectal Cancer

Abstract: Objective: We aimed to study the prognostic role of CpG island methylator phenotype (CIMP) in patients with different stages of colorectal cancer (CRC). Material and Methods: We analyzed CIMP in stage I–IV CRC specimens from patients who were diagnosed between 2005 and 2013. CIMP status was determined using a 5-gene MethyLight-based assay. The clinicopathologic characteristics were reviewed and the overall survival (OS) was compared between patients with CIMP-high CRC and those with CIMP-low/negative CRC. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To gain further insight into the prognostic value of CIMP among CRC patients, we conducted an updated meta-analysis. In this manuscript, we identified 20 recently published studies [ 13 , 28 31 , 35 , 36 , 43 55 ]. When these new studies were incorporated in the present update, the pooled hazards ratios of both OS and DFS/PFS/RFS were similar to those in the previous meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain further insight into the prognostic value of CIMP among CRC patients, we conducted an updated meta-analysis. In this manuscript, we identified 20 recently published studies [ 13 , 28 31 , 35 , 36 , 43 55 ]. When these new studies were incorporated in the present update, the pooled hazards ratios of both OS and DFS/PFS/RFS were similar to those in the previous meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that the prognostic role of CIMP might be variable among different tumor stages. However, based on stratified analyses according to tumor stage, different studies draw distinct or even contrary conclusions [ 13 , 35 , 36 ]. Thus, a subgroup meta-analysis was performed in our updated analysis to address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the majority of human CRCs are characterized by global hypomethylation and promoter-speci c DNA methylation (29), whereas 15-20% of them exhibit the CIMP status, with extensive and co-ordinate patterns of hypermethylation events in numerous CpG islands surrounding the promoter regions of several genes whose transcriptional silencing contributes to onset and progression of CRC (30,31). The prognostic signi cance of CIMP is controversial, with several studies suggesting that CIMP status is an independent prognostic factor of poor outcome (32,33). However, this conclusion is still debated likely due to different de nitions of CIMP among studies with respect to methylation loci and laboratory methods (32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to better de ne the prognostic relevance of promoter hypermethylation events in human CRC, this study was designed to characterize epigenetic signatures helpful to identify mCRCs molecular subgroups with de ned clinical behavior. In such a context, primary-resistant colorectal carcinomas were selected as cases representative of poor outcome (33), based on the evidence that methylation modi cations are key events used by cancer cells to rapidly adapt to unfavorable environments and acquire drug resistance (34,35). Our data suggest that the methylation pro le of 12 functionally methylated genes is predictive of clinical outcome being able to clusterize two independent mCRC cohorts (i.e., the TCGA COAD and the inhouse datasets) in two well-de ned clusters with hypermethylated tumors characterized by worse prognosis and a MSI-like phenotype compared to hypomethylated tumors.…”
Section: Discussionmentioning
confidence: 99%